Double Sequential Defibrillation for Refractory Ventricular Fibrillation: A Case Report. (2nd October 2015) - Lybeck, Aurora M.; Moy, Hawnwan Philip; Tan, David K.
Abstract: A 40-year-old male struck his chest against a pole during a basketball game and had sudden out-of-hospital cardiac arrest. After bystander cardiopulmonary resuscitation, fire and emergency medical services personnel provided six defibrillation attempts prior to emergency department arrival. A 7th attempt in the emergency department using a different vector was unsuccessful. On the 8th attempt, using a second defibrillator with defibrillator pads placed adjacent to the primary set of defibrillator pads, two shocks were administered in near simultaneous fashion. The double sequential defibrillation was successful and the patient had return of spontaneous circulation at the next pulse check. He recovered in the intensive care unit, was discharged home 1 month later, and continues to follow up in clinic over 1 year later with a Cerebral Performance Category score of 1 (short-term memory deficits).